Pengaruh Tenaga Kerja dan Biaya Produksi Terhadap Pendapatan Masyarakat (Studi pada Petani Kopi di Kelurahan Topos Kabupaten Lebong) - Fhatur Heksa Setiawan; Idwal B; Kustin Hartini (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the effect of labor and production costs on the income of coffee farmers in Topos Village, Lebong Regency. The study uses a quantitative approach with field research methods. Primary data was obtained by distributing questionnaires to respondents. The research population consisted of 431 coffee farmers, and the sample was determined using the simple random sampling technique with the Slovin formula, resulting in 82 respondents. Data analysis included descriptive statistics, data quality testing, reliability testing, normality testing, multicollinearity testing, multiple linear regression analysis, and hypothesis testing using t-tests, F-tests, and the coefficient of determination (R²) with the help of SPSS version 26. The results showed that, partially, the labor variable did not have a significant effect on coffee farmers' income. Conversely, the production cost variable had a positive and significant effect, meaning that the higher the production costs incurred, the higher the income obtained. Simultaneously, both variables, namely labor and production costs, were proven to have a significant effect on the income of coffee farmers in Topos Village. This finding illustrates that production cost management plays a more dominant role than labor in increasing farmers' income.